Snouck Hurgronje and the Tradition of Orientalism in Indonesia - Harda Armayanto; Adib Fattah Suntoro; Zen Anwar Saeful Basyari; Nurul Aminah Mat Zain (Tasfiyah: Jurnal Pemikiran Islam, 2023)
This article aims to reveal and analyze the works and thoughts of Snouck Hurgronje's orientalism in Indonesia. Hurgronje was the most influential orientalist in formulating the Dutch Colonialism policy in Indonesia. Unlike most orientalists who only studied Islam through literature studies, Hurgroje also penetrated directly into the Muslim community and mingled with them, he even managed to infiltrate Muslim intellectuals by pretending to convert to Islam. This research is a qualitative study that uses literature to collect data from books, journals, and other documents related to Hurgronje's thoughts. This research found that there is a deep relationship between orientalism and colonialism as seen in Hurgronje's works. Among his most phenomenal orientalist thoughts is his thesis that the Hajj ritual in Islam is a pagan legacy. Hurgronje also made a strategic move in the Aceh War by advising the Dutch East Indies government to separate religion and politics (secularization). According to Hurgronje, if Islam was integrated with politics, it would encourage people's resistance, which was dangerous for the Dutch. In addition, Hurgronje also developed the Receptie theory which aims to dwarf Islamic law and uphold traditional law to clash the two.